Rock ’n’ roll, «nueva ola» and garage rock: an aesthetic explanation of the rise of rock music in Peru - Melgar Wong, Francisco (2023)
In their most widespread texts, peruvian rock historians promote semantic ambiguities around terms as rock ’n’ roll , «nueva ola» and rock music, and leave an explanatory gap in relation to the rise of rock music in Peru. This article clarifies these ambiguities and offers an explanation to the rise of rock music in Peru. The author proposes an aestheric approach based on social functions that musicians and listeners assign to a set of musical parameters in a certain historical context. In the end, the article clarifies the meaning of the terms that designate these music genres, and shows that the rise of rock music in Peru involved the continuity of some features of the genres that preceded it, and the appearance of innovations sufficiently important as to define the birth of a new musical genre in this country.